2021
DOI: 10.15430/jcp.2021.26.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Mechanistic Link between Bisphenol A and Cancer Stem Cells: A Cancer Prevention Perspective

Abstract: Breast cancer is one of the most commonly diagnosed cancers in women [1]. There are well established risk factors for breast cancer, such as genetic alterations, age, family history, life-style, hormone replacement therapy, and obesity [2]. According to the American Cancer Society, more than two thirds of breast cancer at the first diagnosis in women is estrogen receptor (ER)-positive [2]. Extended exposure to estrogen is epidemiologically and experimentally associated with an increased risk of developing brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…As described in our summary and by numerous reviews, BPA modulates ER-mediated effects (KC8) through several different ER subtypes and their downstream signaling pathways. 21,26,28 Modulation of ER is associated with alterations in genes involved in cell immortalization, increased cell invasion (KC9), 19,268,301 induced cell proliferation/ hyperplasia, inhibition of apoptosis, and increased cell migration (KC10). 11,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] This is similar to estradiol, which is thought to act through binding to the ERα, resulting in stimulation of cell proliferation and initiation of mutations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As described in our summary and by numerous reviews, BPA modulates ER-mediated effects (KC8) through several different ER subtypes and their downstream signaling pathways. 21,26,28 Modulation of ER is associated with alterations in genes involved in cell immortalization, increased cell invasion (KC9), 19,268,301 induced cell proliferation/ hyperplasia, inhibition of apoptosis, and increased cell migration (KC10). 11,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] This is similar to estradiol, which is thought to act through binding to the ERα, resulting in stimulation of cell proliferation and initiation of mutations.…”
Section: Discussionmentioning
confidence: 99%
“…21,26,28 Modulation of ER is associated with alterations in genes involved in cell immortalization, increased cell invasion (KC9), 19,268,301 induced cell proliferation/ hyperplasia, inhibition of apoptosis, and increased cell migration (KC10). 11,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] This is similar to estradiol, which is thought to act through binding to the ERα, resulting in stimulation of cell proliferation and initiation of mutations. 302 BPA's effects may be amplified or enhanced by estrogenic BPA metabolites, such as MBP and HCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BPA exposure has been demonstrated to be associated with an increased risk of cancer [ 72 ]. More precisely, BPA does not only stimulate neoplastic proliferation in hormone-dependent tumors by acting as a ligand for hormone receptors, but also through direct regulation of oncogenes and/or tumor-suppressor genes.…”
Section: Bisphenol a Effects On Human Healthmentioning
confidence: 99%
“…Human embryonic cells exposed to low Interaction of Bisphenol A with G Protein: Coupled Receptors -New Paradigms in Breast Cancer DOI: http://dx.doi.org/10.5772/intechopen.101204 concentrations of BPA upregulate the expression of Oct4 and Nanog proteins, two early differentiation markers of mammary epithelial cells [103]. Another possible regulator of CSCs, activated by BPA, is bone morphogenetic protein [104]; it has been suggested that bone morphogenetic protein 2 initiates the transformation of stem cells toward a malignant phenotype [105]. Similarly, the presence of angiotensin II has been verified in breast cancer epithelial cells [102,106] and the stroma [102] and overexpression of AT1 receptor in MCF-7 cells has been associated with an increased capacity for cell migration, invasion, proliferation [101,107], and release of MMP-9 [107], responses associated with phosphorylation of ERK1/2 MAPK [107].…”
Section: Angiotensin Receptorsmentioning
confidence: 99%